Effects of applying wax on the colour, glossiness, and whiteness index values of American Black Cherry (Prunus serotina) wood - Ümit Ayata; Osman Çamlibel (Les)
In this study, the effects of applying wax on the colour, glossiness, and whiteness index (WI*) values of American black cherry (Prunus serotina Ehrh.) wood were investigated. Wax was applied to wooden material surfaces using a brush in one, two, and three layers. Tests were then conducted on surfaces with and without wax. The results were statistically significant according to the multivariate variance analysis. It was determined that the application of wax led to a decrease in L*, ho, and WI* values on the wooden material surfaces (parallel and perpendicular to the fibres), while the a*, b*, and C* parameters increased. In measurements parallel and perpendicular to the fibres, increases were observed in gloss values for two- and three-layer wax applications at 60° and 85°. The ∆L* values were negative when wax was applied in one, two, and three layers, whereas the ∆a*, ∆b*, and ∆C* values were positive. The ∆E* values were determined as 8.41 for one layer of wax, 11.29 for two layers, and 11.59 for three layers. Given the similarity between the ∆E* values of two and three layers of wax, it can be inferred that a third layer may not be necessary.